Authentic leadership in higher learning institution: a case study of International Islamic University Malaysia (IIUM) - Opatokun, Khadijah Adedoyin; Hashim, Che Noraini; Syed Hassan, Sharifah Sariah (Regent University School of Business & Leadership, 2013)
This study investigated the pattern of authentic leadership. The purpose of this study is to test if selfawareness, balanced processing of information, internalized moral perspective, and relational transparency are predictors of authentic leadership among administrative heads at International Islamic University IIUM. An authentic leader reflects the extent to which there is congruence between leader’s actions, intention, moral compasses, self-reflexivity, self-concept, self-development, altruistic actions, authenticity, psychological well-being, and internal regulation. This research is a case study, focusing on data collected from administrative staff at IIUM. The results of the regression indicated that the four predictors (self-awareness, balanced processing of information, internalized moral perspective, and relational transparency) explained authentic leadership. The tested model provides empirical evidence about the pattern of authentic leadership in higher education, thus confirming the presence of authentic leadership in organizations.